KUALITAS PELAYANAN PERPUSTAKAAN PERGURUAN TINGGI KEAGAMAAN ISLAM TERHADAP KEPUASAN PEMUSTAKA (Studi Kasus Perpustakaan Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur’an Sumatera Barat) - Rinaldo Marajari, Muhammad (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This research was conducted at the STAIPIQ Library in Padang City, West Sumatra. This study aims to see the quality of library services on user satisfaction. The research method used is descriptive qualitative. The service quality of the STAIPIQ West Sumatra library refers to the needs of users and user satisfaction. Therefore, good service is a service that can meet the needs and expectations of users, so a good library is a library that can provide services to users quickly and precisely, there are several factors that can improve the quality and satisfaction of service users at an institution, namely: organizational goals, incentive systems used, accountability systems and power structures, as an institution that carries out service activities, the library is obliged to constantly improve the quality of its services so that it can meet the needs of users. Service quality is a comparison between the expectations of service users and the quality of performance. services, in other words that the main factor influencing service quality is the performance of employees whose results are felt by service users, while the quality of service performance is the main activity carried out by a service institution. The services and facilities provided to the user will always be felt and known by the user, giving rise to a certain attitude from the user towards these facilities and services.